Netralitas Asn Dalam Pemilu Dan Pilkada Kabupaten Boyolali Tahun 2024 - Pramudita, Hadian; Wijaya, Geri Meinando Marga; Pramudita, Bintang; Puspaningrum , Puspaningrum (Journal of Administration, Governance, and Political Issues, 2025)
This research discusses the neutrality of Civil Servants (ASN) in the 2024 General Election (Pemilu) and Regional Election (Pilkada) in Boyolali Regency. Elections are one of the main instruments in a democratic system, allowing the public to determine the leaders and policy directions that the government will take. Elections are a means of popular sovereignty conducted directly, publicly, freely, secretly, honestly, and fairly in the Unitary State of the Republic of Indonesia based on Pancasila and the 1945 Constitution. To realize the ideals of Indonesia as stated in the preamble of the 1945 Constitution, which declares that Indonesia needs professional ASN employees, meaning they must be free from political intervention, free from corruption, collusion, and nepotism, and able to provide appropriate public services. The type of research used is normative juridical, which involves examining laws and regulations, legal theories, and jurisprudence related to the issues discussed. This is used as the main approach to explore the law based on legal regulations, by studying and analyzing legal theories, concepts, and principles. Normative research is a process of finding legal rules, legal principles, and legal doctrines to address legal issues. In this case, this approach is used and connected to the problem being researched. The research results show that the principle of ASN neutrality has been regulated through several laws, including Law Number 5 of 2014 concerning Civil Apparatus, but in practice, neutrality is not observed by all ASN in Boyolali Regency. This has resulted in significant impacts on the stability of the government and public services. If the neutrality of ASN in elections and regional elections is implemented, it would strengthen the foundation of a healthy democracy and give the public confidence that every vote carries equal weight in the process of forming a government. There is a need for improvements and strict supervision by the Election Supervisory Board (Bawaslu) of Boyolali Regency during the evaluation of the 2024 elections and regional elections, hoping that oversight of neutrality and the imposition of firm sanctions on ASN who violate neutrality can be more optimal, ensuring that the elections can proceed transparently, honestly, and democratically in the following elections and regional elections.